Reproductive biology of the mud snail (Cerithidea Cingulata), a pest in milkfish ponds in Iloilo, Philippines. - Lantin-Olaguer, Imelda M.
This thesis describes the sexual dimorphism, sex ratio, gonadal maturation, mating, spawning and fecundity of the snail Cerithidea cingulata, in a brackishwater pond in Molo, Philippines. snails ranging 4-41 mm in shell length were sampled monthly from May 1997 to May 1998; 25% were <25mm, 67% were 20-30 mm, and 8% were >30 mm. Sexes are separate and could first be distinguished at 15mm long. Males are aphallic, have narrower shells than females of the same length, and have a bright yellow-orange testes overlying the digestive gland deep inside the shell. Females have more robust shells, an ovipositor at the right side of the foot, and yellow-green ovaries overlying the digestive gland. The sex ratio was one male to two females in the pond population studied. Gonadal maturation was monitored by means of gonadosomatic index (GSI, gonad weight as % visceral weight) and the maturation stages based on the gonad appearance (immature, developing, mature) and histology (immature, developing, mature, redeveloping). GSI increased with snail size, and reached 16% in a 33mmfemale. The smallest mature males and females were 18-19 mm, and most snails>20 mm were mature, spawning, or redeveloping. Histological sections showed all stages of gametogenesis in mature snails. The oocyte size-frequency distributions in mature females showed mostly ova and secondary oocytes, but also oogonia and primary oocytes. Most of the large oocytes occured from February to September. GSI and the frequency of different maturation stages varied the year, with both GSI and the frequency of mature snails highest during the warm months April to August when water temperatures were 24-34 degrees centigrade and salinities were 15-48 ppt. Nevertheless, mature snails occured the whole year, and mating and egg-laying were observed the whole year. Fecundity (=number of oocytes>70 um) increased with size in mature females 20-41 mm; an average 25 mm female produced about 1,500 oocytes and larger females produced a maximum of about 2,500 oocytes. Eggs strings laid on the pond bottom averaged 64 mm long and contained 2,000 eggs 210{ogon}20 um in diameter. The density of eggs trings was highest (80-120/mraised to the 2nd power) in March-Sept. Eggs hatched after 6-7 into planktonic veligers, which in turn settle on the pond bottom 11-12 later as juveniles. Juveniles 2-6 mm long were most abundant in the pond in August-October. The pond sampled had 1-2% organic matter in the sediment the whole year, and the following diel and annual ranges of conditions: water temperatures 23-26degrees centigrade, salinity 15-48 ppt, dissolved oxygen 2-16 ppm, total ammonia 0-0.8 ppm, and pH 7.7-8.8.